FANDOM: STRATEGI KOMUNIKASI PEMASARAN 3.0 UNTUK MELANGGENGKAN FANTASI NASIONALISME MELALUI OLAHRAGA - Heni Indrayani; Sunarto Sunarto (Universitas Bunda Mulia, 2019)
ABSTRACTSpeaking of Indonesian badminton, the support of the supporters cannot be released. Badminton supporters in Indonesia are